Revise igcse: mathematic - Patmore, Mark; Seager, Brian (Letts London, 2008)
Revise IGCSE: Mathematics is a focused revision guide that covers essential mathematical concepts and exam techniques to help students prepare effectively for the IGCSE Mathematics exam.